Mapping the activities of Faith-Based Organisations in Development in Nigeria (2010)
This paper is an outcome of the Religions and Development Research Programme in Nigeria. The rationale for this study is that the nature, scale and activities of faith- based organisations (FBOs) are poorly understood and documented in Nigeria. The aim of the study was, thus, to undertake a mapping exercise of the nature, scale and activities of FBOs in development in Nigeria. The objectives are: (a) To increase awareness of the nature and scale of faith-based contributions to development in Nigeria, (b) To provide the necessary background and contextual information for further studies under other components of the RaD research programme, helping those involved to prepare detailed research proposals and to select geographical locations, faith traditions and FBOs for further study. The methodological approach included the review of documented evidence and structured interviews. The study is of a qualitative character seeking to identify nature, scale, location and activities of faith-based organisations through in-depth interviews with representatives of umbrella organisations and key informants from faith groups. The survey revealed that the number of registered and active FBOs is limited in Nigeria. However, the active ones can be found in almost all the states of the federation, or at the least, in every geopolitical zone of the country. It also revealed that a high proportion of religious organisations provide some human services. Most of the FBOs mobilise and rely on deeply engaged volunteers rather than paid staff, thus delivering services more efficiently than other providers. The key advantage of FBOs is that they have better access to volunteers, which could be used to expand their role in delivering social services. The faith-based organisations also have the advantage that they are located in communities where services are needed. They are also involved in informal networks (e.g., cooperating, coordinating, and working together with other organisations). These increase their delivery of human services. FBOs often have a direct impact on social institutions, such as schools, which socialise people and change values over time. In addition, their jurisdiction often includes a number of areas such as morality, beliefs about the spiritual bases of disease, rules of family life and sexual activity. FBOs are also very active in practical areas of poverty reduction, providing income-generating programmes for members. The paper concludes that, generally, little research has been done on specific operational issues affecting FBOs activities in development. There is need for case studies to specifically examine FBO programmes and their impact, and here longitudinal studies could greatly contribute to the study of an effort primarily oriented toward a long-term horizon. There is also the need to find out if faith-based organisations bring distinctive advantages to community development. The issued could be readily addressed by comparing faith-based and secular organisations active in community development.